2020
DOI: 10.1016/j.earlhumdev.2019.104864
|View full text |Cite
|
Sign up to set email alerts
|

Maternal RhD heterozygous genotype is associated with male biased secondary sex ratio

Abstract: The results of previous studies overwhelmingly suggest that RhD positive heterozygotes express better health status than Rh positive homozygous, especially in RhD negative subjects. This also applies to pregnant women. According to the Trivers-Willard hypothesis, women in better physical condition should have a male-skewed sex ratio. The aim of the present study was to test the hypothesis that RhD positive heterozygous mothers give birth to more sons than daughters. In the present cross-sectional study, we ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Most recently, additional indirect evidence was offered by Kaňková et al (2020), who showed that RhD heterozygous mothers, that is RhD-positive women who gave birth to at least one RhD-negative child, tend to deliver more sons than daughters. According to the Trivers-Willard hypothesis (Trivers & Willard, 1973), females in better physical (or psychological) condition should bear more sons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, additional indirect evidence was offered by Kaňková et al (2020), who showed that RhD heterozygous mothers, that is RhD-positive women who gave birth to at least one RhD-negative child, tend to deliver more sons than daughters. According to the Trivers-Willard hypothesis (Trivers & Willard, 1973), females in better physical (or psychological) condition should bear more sons.…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, we took advantage of the fact that an RhD heterozygote can be easily identified based on the subject's RhDpositive phenotype plus one RhD-negative biological parent (Kaňková et al, 2020). In relatively rich, low fecundity countries like the Czech Republic the vast majority of people know their biological parents' and their own RhD phenotype (Voracek et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Five previous studies had shown associations between Rh-negativity and psychomotor or cognitive functions [43][44][45][46][47] and other four studies had demonstrated the existence of a relation between Rh-negativity and health [48][49][50][51] . Another large-scale study concluded that Rh-negative mothers give birth to significantly more girls than boys: secondary sex ratio 1.37 in primiparous mothers and 1.23 in all mothers 52 . According to the Trivers-Willard hypothesis, this indicates worse health of Rh-negative women.…”
mentioning
confidence: 99%